2006
DOI: 10.1016/j.mbs.2006.03.017
|View full text |Cite
|
Sign up to set email alerts
|

A novel Lie algebra of the genetic code over the Galois field of four DNA bases

Abstract: Starting from the four DNA bases order in the Boolean lattice, a novel Lie Algebra of the genetic code is proposed. Here, the main partitions of the genetic code table were obtained as equivalent classes of quotient spaces of the genetic code vector space over the Galois field of the four DNA bases. The new algebraic structure shows strong connections among algebraic relationships, codon assignments and physicochemical properties of amino acids. Moreover, a distance defined between codons expresses a physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 26 publications
0
47
0
3
Order By: Relevance
“…Several investigators [12,15,17,46] derive genetic Gray codes based on the cube's Hamming distances. The 3D "Genetic Hotels" [16,19,47,48] are projections of the 6-cube onto a "3-cube" in R 3 space, a 3D-version of the codon table with {C,U,A,G} mapped to {0,1,2,3} and the 1st, 2nd and 3rd codon positions plotted on the x, y and z axes respectively, so CCC corresponds with (0,0,0) and GGG with (3,3,3). The hotel "cube" resembles the CodonArray graph, Figure 10, but the hotel has only three edges per row or column, while the graph has six edges per row and is not a geometric object.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators [12,15,17,46] derive genetic Gray codes based on the cube's Hamming distances. The 3D "Genetic Hotels" [16,19,47,48] are projections of the 6-cube onto a "3-cube" in R 3 space, a 3D-version of the codon table with {C,U,A,G} mapped to {0,1,2,3} and the 1st, 2nd and 3rd codon positions plotted on the x, y and z axes respectively, so CCC corresponds with (0,0,0) and GGG with (3,3,3). The hotel "cube" resembles the CodonArray graph, Figure 10, but the hotel has only three edges per row or column, while the graph has six edges per row and is not a geometric object.…”
Section: Discussionmentioning
confidence: 99%
“…The hotel cube can be manipulated with Galois 4-Field algebra (four additions, three multiplications), but does not possess Euclidian symmetries. Different projections onto the hotel result in different 3D-code geometries; for example (C,U,A,G) produces hotel-cube-edges for amino acids encoded by just two codons [16], but (G,U,A,C) does not [48]. Other three-dimensional geometries such as a simple tetrahedral construct with 20 lattice points representing 64 codons [49] also do not preserve the Hamming metric.…”
Section: Discussionmentioning
confidence: 99%
“…for all x, y ∈ L. It follows from (12) and Proposition 3.7(1) that H 1 = H ((x→y)∧x)→y ⊆ H (x⊗(x→y))→y and from (6) that H (x⊗(x→y))→y = H 1 for all x, y ∈ L.…”
Section: Hesitant Fuzzy Prefilters (Filters)mentioning
confidence: 93%
“…Starting from the four DNA bases order in the Boolean lattice, Sáanchez et al [12] proposed a novel Lie Algebra of the genetic code which shows strong connections among algebraic relationship, codon assignments and physicochemical properties of amino acids. Tian [13] introduced an important algebra, so called evolution algebras, and proposed applications in a lot of aspects such as in Non-Mendelian inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…At the genomic level, biology is essentially digital, and so it is not surprising that combinatorics has been used very successfully there, most spectacularly in connection with the Human Genome Project, but also in other areas, such as the study of secondary RNA structures (Bakhtin and Heitsch 2009). Searching the PubMed database of literature related to biomedical research, one now finds papers utilizing Lie algebras (Sanchez et al 2006), the Riemann Mapping Theorem (Hurdal and Stephenson 2009), and methods from algebraic topology (Singh et al 2008) and algebraic geometry (Wang et al 2005;Laubenbacher and Stigler 2004), to name a few topics not traditionally found in the applied mathematics repertoire. As the biological challenges evolve, there is every reason to expect that more and more fields of mathematics will be in a position to contribute new points of view and new approaches.…”
mentioning
confidence: 99%